CONDITION OF FISHERY CAPTURE AND PERCEPTIONS OF FISHERS’ ON CLIMATE CHANGE IN COASTAL AREA OF BANYUASIN II SOUTH SUMATERA - Fedro Try Buana; Desi Aryani; Mirna Fitrani; Yulian Junaidi (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Climate change is a global phenomenon, namely an increase in the earth's temperature as a result of human activities such as the use of fossil fuels and changes in land use. The impact of climate change is a problem faced by fishers that affect the catch of fishers. This study aims to describe the condition of fishery capture and analyze the fishers' perceptions of climate change in the Banyuasin Regency. This research was conducted in Banyuasin II District, Banyuasin Regency, in 5 villages; Marga Sungsang, Sungsang I, Sungsang II, Sungsang III, and Sungsang IV. The method used in this study was a survey and purposive sampling using specific criteria in sample selection. The data obtained in this study consisted of primary data and secondary data. The results showed that the fishers community in Banyuasin Regency has been experiencing the dynamic of temperature, season, and unpredictable rainfall, which impacted daily life activities, such as; the changes in fish catch, sailing time, and the move of fishing spots. The average fisher's perceptions of climate change score from 4 indicators of information, temperature, season, and number of catches were 40.90, which is a high criterion.